Diagnostic accuracy of Japanese posttraumatic stress measures after a complex disaster: The Fukushima Health Management Survey. (9th August 2016) - Suzuki, Yuriko; Yabe, Hirooki; Horikoshi, Naoko; Yasumura, Seiji; Kawakami, Norito; Ohtsuru, Akira; Mashiko, Hirobumi; Maeda, Masaharu; ,
Abstract: Background: The Posttraumatic Stress Disorder (PTSD) Checklist (PCL) has been widely used among traumatized populations to screen people with PTSD; however, the Japanese version of the PCL has yet to be validated. We examined the diagnostic accuracy of the Japanese version PCL‐Specific (PCL‐S) and the abbreviated versions of the PCL‐S among the evacuees of the Fukushima Daiichi Nuclear Power Plant accident. Methods: Fifty‐one participants were recruited from an evacuee and clinical sample. The PCL‐S, Impact of Event Scale‐Revised (IES‐R), and World Health Organization Composite International Diagnostic Interview were administered. Screening properties of the PCL‐S, IES‐R, and abbreviated PCL‐S against PTSD diagnosis, including sensitivity, specificity, and diagnostic efficiency, were calculated. Receiver operating characteristic curves were drawn, and optimal cutoff points were examined. Results: The sensitivity, specificity, and diagnostic efficiency of the PCL‐S were 66.7%, 84.9%, and 79.2%, respectively (at 52, the area under the curve was 0.83). The cutoff point method for the PCL‐S performed better than did the symptom cluster method. The screening properties of the abbreviated versions were comparable with those of the full version. Conclusions: The Japanese version of the PCL‐S showed moderate diagnostic accuracy and improved performance over the IES‐R for PTSD diagnosis based on the Diagnostic and Statistical Manual of Mental Disorders, fourth edition. The Japanese version of the PCL‐S was a reliable and valid measure, and its diagnostic accuracy was reasonable for both full and abbreviated versions.